2011
DOI: 10.1002/pssc.201100468
|View full text |Cite
|
Sign up to set email alerts
|

Halide based MBE of crystalline metals and oxides

Abstract: A halide based growth chemistry has been demonstrated which can deliver a range of transition metals using low to moderate effusion cell temperatures (30‐700 °C) even for high melting point metals. Previously, growth with transition metal species required difficult to control electron beam or impurity inducing metal organic sources. Both crystalline oxide and metal films exhibiting excellent crystal quality are grown using this halide‐based growth chemistry. Films are grown using a plasma assisted Molecular Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Lithium niobite ( ) has been explored for use in memristor based neuromorphic circuitry due to similarities between its lithium ion conduction mechanisms and the mixed electronic-ionic conduction physics of biological neurons [4]. This paper explores the tolerance of lithium niobite to 1.8 MeV proton radiation and the healing mechanisms observed due to highly mobile lithium ions.…”
Section: Self-healing Of Proton Damage In Lithium Niobite ( ) I Intrmentioning
confidence: 99%
“…Lithium niobite ( ) has been explored for use in memristor based neuromorphic circuitry due to similarities between its lithium ion conduction mechanisms and the mixed electronic-ionic conduction physics of biological neurons [4]. This paper explores the tolerance of lithium niobite to 1.8 MeV proton radiation and the healing mechanisms observed due to highly mobile lithium ions.…”
Section: Self-healing Of Proton Damage In Lithium Niobite ( ) I Intrmentioning
confidence: 99%
“…Previous research has shown: a density of states similar to high temperature cuprate superconductors, 4,5 a low temperature superconducting transition, 1 both semiconducting 2 and metallic 6 temperature dependent resistivity, highly mobile lithium ions, 7,8 and memristive behavior. 3,9 X-ray diffraction data identifies lithium niobite as a layered material with niobium oxide layers separated by sheets of loosely bound lithium ions, as shown in Figure 1. Niobium atoms with a nominal valence of 3þ occupy trigonal-prismatic sites between oxygen atoms.…”
Section: Introductionmentioning
confidence: 98%
“…Lithium niobite (LiNbO 2 ) is a sub-oxide of the more common acoustic and optical wave-guiding material lithium niobate (LiNbO 3 ). Lithium niobite is a mixed ion-electron conductor that has been explored for battery [1] and neuromorphic [2] applications. It is a layered [3] semiconductor [1] with loosely bound lithium ions [4,5].…”
Section: Introductionmentioning
confidence: 99%